Penggunaan Media Audiovisual Dalam Melatih Teknik Pernapasan Siswa Pada Ekstrakurikuler Paduan Suara di SMP Negeri 22 Padang - EMPINTANTA GINTING; Esy Maestro (EDUMUSIKA, 2023)
This study aims to find out how the use of audiovisual media in training students' breathing techniques in extracurricular choirs at SMP Negeri 22 Padang. This type of research is qualitative with a descriptive analysis approach. The research instrument was the researcher himself and assisted by supporting instruments in the form of laptop stationery, LCD projectors and mobile phones. The data in this study uses primary data and secondary data. The techniques used in data collection are literature study, observation, interviews and documentation. The steps to analyze the data are identifying the data, classifying the data, describing the data, analyzing the data and concluding the data. The results showed that the implementation of the extracurricular choir at Padang 22 Public Middle School had been carried out and was quite good, even though the teacher trainers did not have a background in music and only understood a little about breathing techniques, by utilizing audiovisual media breathing techniques students could be trained well. So that students already know what are the types of breathing in singing, students' breathing becomes long because they are often trained with the flat tire technique, students are also skilled in breathing quickly when singing songs with fast tempo because of lightning breathing exercises and breathing exercises. panting, and practice inhaling 4 times and exhaling 8 times. So that the phrases and intonation when singing are also not disturbed anymore.